Thermography as a tool for evaluation and prevention of injuries in athlete - Matteoli, S.; Fulceri, S.; Pasquini, G.; Corvi, A. (Gait and Posture, 2018)
Introduction: Skeletal muscles constitute approximately 40% of the human body weight. About 75% of the metabolic energy is not employed as mechanical work but it is lost in heat, released as infrared radiation. In the biomedical field, the idea of using infrared thermography (IT) for evaluating muscles health condition and preventing potential injuries has developed more and more [1,2]. The aim of this work is to evaluate muscle conditions (pre and post training) of volleyball players legs by means of IT for identifying subjects who could be at risk of injury. Methods: A team of male volleyball players (27,6 years) were subjected to thermographic acquisitions (FLIR 320A, FLIR Systems, Oregon, USA) once a month, for 4 months. None of the athletes had any injuries within the last two months before the test. Athletes were required not to: use body lotions, smoke, drink coffee, have massages and train in the 24 hours before thermographic test [2]. They had to fulfil a questionnaire in order to achieve personal information such as: weight, height, age, health condition, dominant leg, habitual training (with focus on the week before the test), and past injuries (if any). Thermographic acquisitions were performed in a climate controlled-room, illuminated with neon lights and with subject placed at 2m from the camera. The temperature of both lower limbs (front and back) was recorded in two different conditions: 1) at rest (after 20 minutes of acclimatization, t0); 2) after training (t1). Furthermore, each athletewassubjected to plicometry (4-Site Skinfold, Jackson & Pollock). During the 4 weeks following the thermographic test a follow-up was carried out to monitor the physical condition of the athletes and to check for possible signs of painful symptoms or injuries. Post-image processing was carried out applying a custom semi-automatic procedure developed in Matlab (MathWorks Inc., USA) which allows normalizing a subjects thermographic profile [3] and calculating the mean and maximum temperature of each muscle/joint located in the thighs, knees and lower legs (front and back). In order to use thermography as a preventive tool, it was necessary to establish the healthy muscular thermal behaviour of an athlete that can be described by two parameters: 1) symmetry of the thermal distribution between the two limbs; 2) thermal gradient of the two symmetrical limbs recorded at t0 and t1. When the temperature difference between right and left ROIs exceeded 0.8 .C [3] and/or the thermal gradient exceeded 0.8 .C [3], then the district(s) involved needs to carefully monitored during the follow-up as it might be subjected to injuries.Results: The study pointed out a negative correlation between the percentage of fat measured on the tight and the maximum temperature of the rectus femoris, showing that adipose tissue, interposing between muscle and skin attenuates the emission of infrared radiation since it acts as a thermal insulation. The temperature analysis showed that two athletes had their right knee at risk of injuries, as the temperature difference between the right and left ROI was up to 3 .C. Both athletes confirmed pain and discomfort at their right knee during the follow up. No injuries happened thanks to prevention techniques followed by both athletes. Discussion: Infrared thermography is a non-invasive technique that allows monitoring the superficial temperature of athletes. This study points out that thermography paves the way to be a tool for injury prevention.